Nurses experience of caring for patients with COVID-19: A phenomenological study - Al-amer, Rasmieh; Darwish, Maram; Malak, Malakeh; Ali, Amira Mohammed; Al weldat, Kadejeh; Alkhamees, Abdulmajeed; Alshammari, Khaled S.; Abuzied, Yacoub; Randall, Sue (Frontiers in Psychiatry, 2022)
Introduction COVID-19 has impacted all dimensions of life and imposed serious threat on humankind. Background In Jordan, understanding how nurses experienced providing care for patients with COVID-19 offers a framework of knowledge about similar situations within the context of Arabic culture. Aim To explore nurses' experience with providing hands-on care to patients with active COVID-19 infection in an Arabic society. Methods A descriptive phenomenological study interviewed 10 nurses through a purposive sampling approach until data saturation was reached. The research site was hospital designated to receive patients with active COVID-19 infection. Semi-structured interviews were used to collect the data. Findings Three themes were generated from the data: the impact of the COVID-19 outbreak on nurses' health; unfamiliar work and social environments; and conforming to professional standards. Discussion There are specific risks to the physical and mental wellbeing of nurses who provide hands-on care to patients with COVID-19 in an Arabic society. Implication for nursing and health policy Health care institutions should consider establishing programs that promote nurses' wellbeing and support their productivity in a crisis. A danger pay allowance should be considered for nurses during extraordinary circumstances, such as pandemics.